Leafing, flowering, fruiting and initial growth of 'cagaiteira', in Planaltina, DF, Brazil - Sano, Sueli Matiko; da Fonseca, Carlos Eduardo Lazarini; Ribeiro, José Felipe; Oga, Fernanda Marina; Luiz, Alfredo José Barreto (Pesquisa Agropecuaria Brasileira, 1995)
The phenophases of leafing, flowering and fruiting of 'cagaiteira' (Eugenia dysenterica Mart), Myrtaceae, were studied in a Cerrado vegetation at Planaltina, DF, Brazil, from November 1985 to January 1992. The peak of leafing activities, senescence and emission of new leaves occurred in August, by the end of dry season. This peak of formation of leaves was simultaneous to flowering activities. The fruit maturation occurred during September-October. 'Cagaiteira' seedlings were cultivated in plastic bags, under two light intensities: 100% of natural light in an open field nursery, and 50% of natural light in a woven nylon covered lath house. Growth analysis performed by destructive method was done every 35 days for a 140-day period. Seedlings showed a better growth in natural light conditions. Production of dry matter was higher in roots followed by leaves and stems. Five months old seedlings had an average of 11.5 cm of height, 7.8 leaves, and 50.6 dm<span style="line-height: 115%; font-family: ";Calibri";,";sans-serif";; font-size: 13.5pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: PT-BR; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">2 of leaf area.